DEVELOPMENT OF CHEMICAL E-MODULES BASED ON PAPUA LOCAL WISDOM ON REDUCTION AND OXIDATION REACTION MATERIALS TO INCREASE STUDENT LEARNING OUTCOMES - Tiurlina Siregar; Marice Karubaba; Johnson Siallagan; Mamberuman M. Inggamer (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2022)
This study aims to find out how to make chemical e-modules based on Papuan local wisdom, development of chemical e-modules based on Papuan local wisdom, feasibility of chemical e-modules based on Papuan local wisdom, improvement of science process skills (KPS) and student learning outcomes. class X science using e-module chemistry based on local Papuan wisdom on the material of reduction and oxidation reactions. The research method used is research and development (R and D). This research was conducted in class X IPA1 SMA YPPK Teruna Bakti Jayapura with a total sample of 28 students. E-chemistry module based on Papuan local wisdom on the material of reduction and oxidation reactions through the ADDIE stage arrangement with the use of the school environment can increase students' chemistry learning outcomes with the n-Gain test obtained an average of 0.74 with a high category.